IMPLEMENTASI PERATURAN TENTANG KEDUDUKAN NOTARIS YANG MENJADI ANGGOTA LEGESLATIF MENURUT UNDANG-UNDANG JABATAN NOTARIS DAN UNDANG-UNDANG PEMILIHAN UMUM - Mukhlisin, Thoad Bakhtiar; Riyanto, Sigid ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This is a study on The Implementation of Regulation About The Position of Notary Becoming The Member of Legislative According to Regulation About Notaryâs Position And Regulation of General Election discussing especially about the legal status of notary becoming the member of legislative, the implementation of regulation about notary becoming the member of legislative and the position of notary after finishing his or her job as the member of legislative. The type of the research used was empirical juridical research. An empirical juridical research is a research based on the secondary data as its initial data, which is then continued with primary or field data. This research took subject of notary becoming the member of legislative in Sleman Regency. Data collecting technique used in this research was in the form of list of questions used as the guidance in the interview carried out by questioning and answering directly to the research subject and source person. The data obtained was analyzed descriptively and qualitatively. The result of The Research About The Implementation of Regulation About The Position of Notary Becoming The member of Legislative According to The Regulation of Notaryâs Position And Regulation of General Election were: 1) A notary becoming the member of legislative has status of furlough. The word furlough in regulation of notaryâs position and the word of does not practice in regulation of general is meant as stop temporary as a notary according to the license of furlough released, so that the two regulations are not in opposite. During becoming the member of legislative he or she does not run his or her job and authority as notary, 2) A notary becoming the member of legislative has a must to take furlough. The furlough is proposed to Majelis Pengawas Pusat (Central Monitoring Council). This is because the furlough is more than one year. The related notary appoints a substitute to run the job and authority as notary. The mechanism to take the furlough license carried out and the accepted furlough license are appropriate with the existing regulation, 3) After finishing as the member of legislative, automatically the job and the position of notary will be back. The notary can directly do the job and authority as notary without proposing the license of appointment.